THEATRE STAGES OF INTRAMURAL DISTRICT OF LATE OTTOMAN CAPITAL AND GEDIKPASA THEATRE - Kula, Seda; Gurbuz, Zuelal (E.U. Printing And Publishing House, 2023)
In the 19th century, especially after the Tanzimat, gradually steered the Ottoman society's demand for traditional entertainments , leisure places towards theater. The Ottoman capital's theaters, emerging primarily in the Pera region, where foreigners lived , especially with opera performances, penetrated in the second half of the century into Surici area, where the Muslim population was densely populated, with primarily oral theater performances. In this process, while the main opera theater in Pera was the Naum, the major theater establishment of Surici stood out as Gedikpasa Theater.The gradual positioning of shabby stages of intramural Direklerarasi quarter as an alternative to Pera theatres was a development parallel to the willpower of not settling for merely theatres in predominantly non-Muslim Pera, but of extending the scope of this facility to address the whole of the Ottoman society and easing access to this means of communication. Consequently the establishment of Gedikpasa Theatre in the vicinity of intramural Direklerarasi shabby stages and its endowment with a ten-year privilege of stage performance in Turkish language would channel the traditional entertainment practices of Surici area to a new medium. This new spectacle practice along with its spaces that people participated voluntarily and with their individual preferences attended, thus formed a facilitating means of confronting the Ottoman society with some significant components of modernity. Gedikpasa Theater offered a new and effective communication opportunity to both the government and the society in Ottoman modernization. In this respect, it is aimed to examine the concepts of modernity presented to the public with theatrical activity at Gedikpasa Theater in Surici, which is predominantly Muslim, and the events that develop depending on these presentations because it helps us to examine, to some extent, the consequences of the Ottoman government and society's confrontation with the modernization process. The concepts of modernity that Ottoman modernity faced through theater appear in the form of creating a common cultural language, developing the idea of individual rights and citizenship, making propaganda, revealing secular concepts, and giving women new and more comprehensive roles in social and cultural life. Although the Gedikpasa Theatre was destroyed in 1884, it introduced the modern and especially Turkish oral theater course in Surici to the Muslim Ottoman society and fulfilled its mission to create a demand for theater and Surici region has increased its vitality in terms of theater, Sehzadebasi region near Gedikpasa region has gained a new vitality.In any case, Gedikpasa Theater, played a remarkable role in the modernization of Surici's civil life and formed an important basis for the government's approach to theater activities and spectacles, for these reasons Ottoman modernity was examined through the events and performances in this theater.This research was carried out via an extensive scanning of the existent literature on Ottoman theaters and Gedikpasa Theater, as well as historical maps and archive documents.
GEÇ OSMANLI BAŞKENTİNDE SURİÇİ SAHNELERİ VE GEDİKPAŞA TİYATROSU
Keywords: Ottoman Theatre; Gedikpasa Theatre; Sehzadebasi; Direklerarasi; Naum Theatre; Late Ottoman leisure spaces